Soil water effect on crop growth, leaf gas exchange, water and radiation use efficiency of Saccharum spontaneum L. ssp. aegyptiacum (Willd.) Hackel in semi-arid Mediterranean environment - Scordia, Danilo; Testa, Giorgio; Cosentino, Salvatore L.; Copani, Venera; Patanè, Cristina (Italian Journal of Agronomy, 2015)
Great effort has been placed to identify the most suited bioenergy crop under different environments and management practices, however, there is still need to find new genetic resources for constrained areas. For instance, South Mediterranean area is strongly affected by prolonged drought, high vapour pressure deficit (VPD) and extremely high temperatures during summertime. In the present work we investigated the soil water effect on crop growth and leaf gas exchange of Saccharum spontaneum L. ssp. aegyptiacum (Willd.) Hackel, a perennial, rhizomatous, herbaceous grass. Furthermore, the net increase of biomass production per unit light intercepted [radiation use efficiency (RUE)] and per unit water transpired [water use efficiency (WUE)] was also studied. To this end a field trial was carried out imposing three levels of soil water availability (I100, I50 and I0, corresponding to 100%, 50% and 0% of ETm restutition) under a semi-arid Mediterranean environment. Leaf area index (LAI), stem height, biomass dry matter yield, CO2 assimilation rate, and transpiration rate resulted significantly affected by measurement time and irrigation treatment, with the highest values in I100 and the lowest in I0. RUE was the highest in I100 followed by I50 and I0; on the other hand, WUE was higher in I0 than I50 and I100. At LAI values greater than 2.0, 85% photosynthetically active radiation was intercepted by the Saccharum stand, irrespective of the irrigation treatment. Saccharum spontaneum spp. aegyptiacum is a potential species for biomass production in environment characterized by drought stress, high temperatures and high VPD, as those of Southern Europe and similar semi-arid areas.